Sand Improvement by Surface Percolation Method Using Urease-Containing Substance Extracted from Soybean Seed - Amirreza Pirghazani; Hooshang Katebi; Hossein Samadi Kafil; Ahmad Fahmi (Applied and Environmental Soil Science)
Background. In recent decades, the microbial and plant-derived urease have been used for sand stabilization by the calcium carbonate precipitation method, especially with Sporosarcina pasteurii. However, calcium carbonate precipitation using plant-derived urease has received less attention. Purchasing the extracted and purified commercially available plant-derived urease for the sand improvement is costly. The plant-derived urease-containing crude extract (enzyme substance) is cheaper than purified (commercial) urease. In the present study, the feasibility of sand improvement by enzyme-induced calcium carbonate precipitation method was investigated with urease-containing crude extract (extracted from soybean). Methods. The distilled water, instead of phosphate buffer, was used to provide the main enzyme extraction medium. Also, the effects of temperature, time, and dilution on the activity of the urease-containing crude extract by the electrical conductivity meter were investigated. Results. The results showed that the extraction temperature had a significant effect on the behavior of the enzymes, and according to the results, the temperature range between 19 and 25°C is suitable for the enzyme extraction. The four-layer surface percolation method was used to improve the sand, and 0.75 equimolar (eqM) concentration of urea-CaCl2 cementation solution is suitable for sand improvement using the UCE extracted from soybean seed. Conclusion. Silica sand was successfully improved by the EICP method using the four-layer surface percolation method, and significant unconfined compressive strength and elasticity modulus were obtained. XRD and XRF analysis also confirmed the successful precipitation of calcium carbonate between the sand particles.